The APOB gene polymorphism in the pathogenesis of gallstone disease in pre- and postmenopausal women - Rudzińska, Karolina; Bogacz, Anna; Kotrych, Daniel; Wolski, Hubert; Majchrzycki, Marian; Seremak-Mrozikiewicz, Agnieszka; Kosiński, Bogusław; Czerny, Bogusław (Menopause Review/Przegląd Menopauzalny, 2015)
Aim of the study: The decrease in estrogen levels in the postmenopausal period changes the lipid profile by the expression of hepatic genes related to metabolism of cholesterol and bile acid synthesis that could be important in the pathogenesis of cholelithiasis. The aim of the study was to determine the APOB gene 7673C>T and 12669G>A  polymorphisms in the pathogenesis of gallstones and analysis of the composition of gallstones in pre- and postmenopausal women. Material and methods : The study group consisted of 94 women qualified to the laparoscopic cholecystectomy while the control group consisted of 81 women in whom gallstones and other changes in the bile ducts were excluded. Gallstones composition analysis was performed using commercially available assays. The prevalence of the APOB gene polymorphisms was determined using the polymerase chain reaction and restriction fragment length polymorphism (PCR-RFLP). Results: When assessing the composition of gallstones in pre- and postmenopausal women, we observed differences in the studied parameters. Analysis of genetic variants of APOB gene 7673C>T and 12669G>A  polymorphisms showed no significant statistical differences between studied groups and controls. Conclusions : Analysis of 7673C>T and 12669G>A  polymorphisms showed no relationship between specific genetic variants and the risk of gallstones in pre- and postmenopausal women, pointing to the fact that the investigated polymorphisms are not relevant as prognostic factors in gallstone disease in the Caucasian population. Because of the possible contribution of a variety of factors in gallstones pathogenesis the studies are required to take account of additional environmental factors, what may indicate different occurrence between investigated polymorphisms, gallstone disease development and gallstones composition in Caucasians.